In support of a wide notion of media accessibility: Access to content and access to creation - Romero-Fresco, Pablo (Journal of Audiovisual Translation, 2025)
The prevailing narrow consideration of media accessibility (MA) as concerning only persons with sensory disabilities poses a series of epistemological and terminological issues, and limits the potential of MA to instigate social change. This article supports a wider view of MA that encompasses both people with and without disabilities who need access to audiovisual content. To articulate this wide notion of MA, a distinction is made between access to content and access to creation (Dangerfield, 2017), and examples are drawn from two emerging disciplines: interlingual respeaking and accessible filmmaking (AFM). As far as access to content is concerned, interlingual respeaking can contribute to making MA more visible, forcing hearing audiences to share the same need for access as audiences with hearing loss. As for AFM, by proposing the integration of translation and accessibility as part of the filmmaking process, it provides a platform for deaf, blind and foreign audiences, as well as other groups, to join forces and increase their visibility within the film industry. However, a wide notion of MA must also include access to creation, that is, access to equipment, funding and job opportunities that can enable persons with sensory disabilities to create audiovisual products which, it is argued, can provide a more inclusive and empathetic audiovisual experience than the current model of MA. Correction notice: Please note that this article was modified on 13 February 2025 at the request of Miguel Ángel Font to clarify that the film Xmile (Font, 2016) was not influenced by the principles of Accessible Filmmaking.